Structure of the Plasmodium falciparum Triosephosphate Isomerase−Phosphoglycolate Complex in Two Crystal Forms: Characterization of Catalytic Loop Open and Closed Conformations in the Ligand-Bound State - Parthasarathy, S; Ravindra, G; Balaram, Hemalatha; Balaram, P; Murthy, M. R. N (Biochemistry (Easton), 2002)
Triosephosphate isomerase (TIM) has been the subject of many structural and mechanistic studies. At position 96, there is a highly conserved Ser residue, which is proximal to the catalytic site. Thus far, no specific role has been ascribed to this residue. Plasmodium falciparum TIM (PfTIM), a fully catalytically active enzyme, is unique in possessing a Phe residue at position 96. The structure of PfTIM complexed to phosphoglycolate (PG), a transition state analogue, has been determined in an effort to probe the effects of the mutation at residue 96 on the nature of inhibitor−enzyme interactions and the orientation of the critical catalytic loop (loop 6, residues 166−176) in TIM. Crystal structures of PfTIM complexed to phosphoglycolate in orthorhombic (P212121) and monoclinic (C2) forms were determined and refined at resolutions of 2.8 and 1.9 Å, respectively. The P212121 form contains two dimers in the asymmetric unit. In the C2 form, the molecular and crystal 2-fold axes are coincident, leading to a monomer in the asymmetric unit. The catalytic loop adopts the open state in the P212121 form and the closed conformation in the C2 crystal. The open conformation of the loop in the P212121 form appears to be a consequence of the Ser to Phe mutation at residue 96. The steric clash between Phe96 and Ile172 probably impedes loop closure in PfTIM−ligand complexes. The PfTIM−PG complex is the first example of a TIM−ligand complex being observed in both loop open and closed forms. In the C2 form (loop closed), Phe96 and Leu167 adopt alternative conformations that are different from the ones observed in the open form, permitting loop closure. These structures provide strong support for the view that loop closure is not essential for ligand binding and that dynamic loop movement may occur in both free and ligand-bound forms of the enzyme.